2019
DOI: 10.1038/s41598-019-38862-7
|View full text |Cite
|
Sign up to set email alerts
|

Real time observation of binder jetting printing process using high-speed X-ray imaging

Abstract: A high-speed synchrotron X-ray imaging technique was used to investigate the binder jetting additive manufacturing (AM) process. A commercial binder jetting printer with droplet-on-demand ink-jet print-head was used to print single lines on powder beds. The printing process was recorded in real time using high-speed X-ray imaging. The ink-jet droplets showed distinct elongated shape with spherical head, long tail, and three to five trailing satellite droplets. Significant drift was observed between the impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(64 citation statements)
references
References 46 publications
(35 reference statements)
5
59
0
Order By: Relevance
“…The x-component of the droplet impact velocity for this case is ux = 0.127 m/s. In agreeance with the findings in [29], a significant number of ballistic particle ejections were observed. Furthermore, several tests were performed with a lower vertical impact speed (uz = 2.95 m/s) and particle ejections were still prevalent, albeit with reduced occurrences.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The x-component of the droplet impact velocity for this case is ux = 0.127 m/s. In agreeance with the findings in [29], a significant number of ballistic particle ejections were observed. Furthermore, several tests were performed with a lower vertical impact speed (uz = 2.95 m/s) and particle ejections were still prevalent, albeit with reduced occurrences.…”
Section: Resultssupporting
confidence: 92%
“…In Ref. [29], high-speed imaging of the fluid-particle interaction in BJ3DP was performed with synchrotron X-rays using the Advanced Photon Source at Argonne National Laboratory. With this approach, an X-ray beam passes completely through the powder bed and is converted to visible light on the opposite side.…”
Section: Fluid-particle Interaction In Bj3dpmentioning
confidence: 99%
“…Indeed, the two reasons that lead to porosity are (i) jetting of binder on the build powder surface, where powder is removed by a ballistic effect, and (ii) viscous flow during the sintering process [48,49]. A similar behavior has been reported by Myers [50] and Parab et al [50,51] after sintering 3D printed SiO 2 parts. Myers in his work, observed the samples shrinked at least 13% in Z direction and 10% in X-Y surface when used powder of particle size 48 μm [50].…”
Section: Resultssupporting
confidence: 60%
“…The increase in ink viscosity reduces such phenomena [29]. The impact of the droplets on the powder bed may lead to additional inaccuracies [30]. A study with anatomic models using BJ technology reported a mean absolute error of 0.32 mm (variance of 0.054 mm) for accuracy for structures above 10 mm in size [3].…”
Section: Discussionmentioning
confidence: 99%